In pursuit of endogeneity: an analysis of selected post-independence Shona poetry - Tembo, Charles; Mutasa, Davie E. (Southern African Journal for Folklore Studies, 2022)
Relevant history and culture are indispensable to the struggles for authentic liberation. Therefore, it is the duty of writers to affirm this fact. This effort by writers is an Afrocentric pursuit of the affirmation of endogeneity in post-independence Shona poetry. The poetry demonstrates the poetsâ€™ intense interest in rootedness and dispel dislocation as an unnecessary luxury. As the exegesis unfolds, it is revealed that the poets exemplify and authenticate commitment to writing against alterity and the ideology of Eurocentrism and what it stands for. In fact, the selected poetry is applauded for its ability to affirm endogeneity. It is poetry of a struggle against the machinations of the ideology of Eurocentrism. It turns out to be poetry devoted to â€œremembering the dismemberedâ€ in a world riddled with imperialism and foreign domination. Reconnecting the audience with their life-furthering historical tradition is cast as a literary imperative